Temperature-dependent abrasivity of Bukit Timah granite and implications for drill bit wear in thermo-mechanical drilling - Ji, Yinlin (2022)
Thermo-mechanical drilling combines the advantages of flame thermal treatment and rotary head drilling to achieve a high penetration rate in granitic rocks and a low wear rate of drill bits. This drilling strategy has been recognized as a potential technique to develop deep geothermal energy, but further improvement is still needed to optimize the drilling efficiency, such as the reduction in drill bit wear in thermally treated rocks. We use the Cerchar abrasivity test to investigate the abrasivity characteristics of Bukit Timah granite after the thermal treatment at different high temperatures. The Cerchar abrasivity index (CAI) decreases from 3.5 at 25 °C to 3.0 at 400 °C, remains constant between 400 and 600 °C and subsequently increases to 4.1 at 800 °C. Based on the meso-scale and micro-scale observations using polarizing microscope, 3D scanner and scanning electron microscope, the reduction in CAI value at lower temperatures is due to the abrasive wear of stylus tip, while the mechanical interaction between the stylus cone and abrasive minerals causes the increase in CAI value at higher temperatures. The Cerchar abrasivity test results indicate that overheating rocks may result in the exposure of drill bits to more abrasive minerals and enhance drill bit wear.